2011
DOI: 10.1128/iai.01235-10
|View full text |Cite
|
Sign up to set email alerts
|

Protective Role of Akt2 in Salmonella enterica Serovar Typhimurium-Induced Gastroenterocolitis

Abstract: The Salmonella effector protein SopB has previously been shown to induce activation of Akt and protect epithelial cells from apoptosis in vitro. To characterize the role of Akt2 in host defense against Salmonella enterica serovar Typhimurium infection, wild-type (WT) mice and mice lacking Akt2 (Akt2 knockout [KO] mice) were infected using a Salmonella acute gastroenteritis model. Infected Akt2 KO mice showed a more pronounced morbidity and mortality associated with higher bacterial loads in the intestines and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 65 publications
1
19
1
Order By: Relevance
“…In a polymicrobial sepsis model, defective M1 response rendered Akt2 mice more susceptible to the disease whereas the robust M1 response of Akt1 −/− mice resulted in improved bacterial clearance. Our results are further supported by an earlier study showing that deletion of Akt2 renders mice more susceptible to Salmonella enterica infection (21). These findings support the role of macrophage polarization in the development of inflammatory diseases, and they show that Akt1 and Akt2 play central but opposite roles in the control of macrophage responsiveness and inflammation.…”
Section: Discussionsupporting
confidence: 80%
“…In a polymicrobial sepsis model, defective M1 response rendered Akt2 mice more susceptible to the disease whereas the robust M1 response of Akt1 −/− mice resulted in improved bacterial clearance. Our results are further supported by an earlier study showing that deletion of Akt2 renders mice more susceptible to Salmonella enterica infection (21). These findings support the role of macrophage polarization in the development of inflammatory diseases, and they show that Akt1 and Akt2 play central but opposite roles in the control of macrophage responsiveness and inflammation.…”
Section: Discussionsupporting
confidence: 80%
“…Gut inflammation plays a crucial role in the development of reactive arthritis following intestinal infection (28). TNF-␣ and IL-17 are among the most prominent cytokines induced soon after Salmonella infection (17,35), and they are also linked to the generation of arthritis (39). With this in mind, we analyzed the expression of TNF-␣ and IL-17 in the large intestine by qPCR 48 h after Salmonella inoculation.…”
Section: Resultsmentioning
confidence: 99%
“…When regulated, the programmed death of infected cells and the degrading action of ubiquitin-specific peptidases facilitate the clearance of systemic Salmonella infection (Jiang and Zhijian, 2012;Redmond et al, 2011). Excessive inflammatory actions, however, can result in epithelial damage that enhances the ability of Salmonella to further invade the area of infection (Kum et al, 2011). Using the murine model, Parent and Eichacker (1999) reported that a disproportionate accumulation of neutrophils and monocytes results in the release of toxic levels of proteases and reactive oxygen intermediates.…”
Section: Discussionmentioning
confidence: 99%